Minat Generasi Muda untuk Menggunakan Jasa di Bank Syariah Indonesia - Rizal, Azza Nazilla; Bustami, AlekWissalam (Masoem University, 2025)
This study reveals that IAIN Kerinci students' awareness of Islamic banking services is still limited, mainly due to their lack of knowledge about the Islamic banking system and services. Although most students have a good understanding of the basic concepts of Islamic banking, their limited knowledge of the mechanisms and actual services makes them less interested in using Islamic banking services. In addition, external factors such as the lack of ATMs in Sungai Penuh City and the lack of convenience and communication between banks and students also contribute to this low level of interest. This study aims to: (1) Identify the level of awareness among students at IAIN Kerinci regarding the use of Islamic banking services. (2) Analyze the strategies used by Islamic banks in improving the quality of their products and services to students. (3) Identify the factors that influence the interest of IAIN Kerinci students in using Islamic banking services. Data analysis was conducted using a qualitative descriptive approach, namely by collecting data through observation, interviews, and documentation. A decentralized model was used to carry out the data analysis process, which included domain analysis, taxonomy, composition, and cultural themes. To ensure the accuracy of the research results, the researchers also applied various data verification and triangulation methods. Research shows that Islamic banks still need to improve service quality and expand access in order to better meet the needs of students and the wider community. Thus, the lack of communication, limited access, and service quality are the main obstacles that cause students to be less interested and reluctant to use Islamic banking services at this time.